Pemanfaatan Limbah Feses Dan Urin Sapi Sebagai Alternatif Bahan Bakar Skala Rumah Tangga Di Sekitar Hutan Camplong, Kabupaten Kupang - Jemseng C Abineno; Aoliab Aoetpah; Yofris Puay; Musa Frengkianus Banunaek (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The objective of this community service was to introduce biogas as an alternative house hold fuel and lighting by using beef cattle pen waste at Camplong forest area, Kupang Regency East Nusa Tenggara Province through integrated farming system. Methods applied were survey, interview, agricultural extension, demonstration and practical work involving 31 farmers on site. Data were descriptively analysed to offer an alternative solution toward feed supply, the used of fuel wood and food crop farming practice of participants. The result was the realization of farmers work pattern by integrating food crop plant, raising cattle and the use of alternative biogas as a source of fuel and lighting. It can be concluded that farmers at the area of Camplong Kupang Regency are able to integrate crop farming and cattle raising by using the available resources through community service.